1968
DOI: 10.1080/00288233.1968.10431428
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of shading and of nitrogen fertiliser on the chemical composition of freeze-dried and oven-dried herbage, and on the nutritive value of oven-dried herbage fed to sheep

Abstract: 1968) Some effects of shading and of nitrogen fertiliser on the chemical composition of freezedried and oven-dried herbage, and on the nutritive value of oven-dried herbage fed to sheep, ABSTRACT An experiment is described in which the nutritive value and chemical composition of oven-dried herbage from shaded perennial ryegrass pasture (SR) were compared with those of unshaded ryegrass (R), shaded + nitrogen-fertilised (SR + N), and unshaded + nitrogenfertilised (R + N) ryegrass herbage, and with those of whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…of lignin content and its related enzymes activities (Hight et al, 1968;Marchiori et al, 2014). In the present study, the lodging percentage and lodging index increased with the increase of nitrogen fertilizer and planting density.…”
Section: Discussionmentioning
confidence: 61%
“…of lignin content and its related enzymes activities (Hight et al, 1968;Marchiori et al, 2014). In the present study, the lodging percentage and lodging index increased with the increase of nitrogen fertilizer and planting density.…”
Section: Discussionmentioning
confidence: 61%
“…10). Many results have shown that in vitro digestibility of grasses is reduced under low light intensity and this is associated with reduced digestibility of cell wall constituents (Hight et al 1968). However, other studies have obtained less conclusive results with both increases and decreases in digestibility of herbage grown in a shaded environment (Wilson 1988).…”
Section: Nutritive Valuementioning
confidence: 98%
“…Shading usually reduces the total non-structural carbohydrate of grasses, but has variable (positive and negative) effects on cell wall content and composition, lignin and in vitro digestibility of plant dry matter (Wilson 1988). According to Hight et al (1968), soluble carbohydrate content decreased by 3.7% units and dried forage digestibility by 0.6-3.6% units during a short shading period of time (2-3 days at 22% light transmission). However, Norton et al (1991) found a small nonsignificant decrease in soluble carbohydrate and a decrease in in vitro dry matter digestibility.…”
Section: Nutritive Valuementioning
confidence: 99%
“…There were, however, differences among legumes (Table 1), with the highest DM percentages occurring in Hawaiian Giant and kaimi clover and the lowest in Siratro (as low as 16.2% DM at 45 and 27% full sun). Low DM concentrations per se are not likely to cause problems, however they are associated with low carbohydrate concentrations in grasses (Hight et al, 1968).…”
Section: Dry Matter Percentagementioning
confidence: 99%